Legal Awareness of Online Motorcycle Taxi Drivers “Gojek” Related to Their Participation in the Workplace Accident Insurance and Death Insurance Program in Surabaya City - Kamila Fakhriyah Aris; Mahendra Wardhana; Ibtisam Mumtaz Khairunnisa (Universitas Negeri Surabaya, 2024)
The BPJS Law in article 14 states,